Glycemic control with four way model approach in rural area patients - Lodhi, MD. Mansoor Ali Khan (International Journal of Research in Medical Sciences, 2019)
Background: It is very important to keep the Glucose levels under control continuously and without any holidays. Type 2 diabetes is increasingly common in the industrialized world. Tight glycemic control attempts to rigidly glucose control levels (A1c: 6.5% -7.0% or lower). Maintaining tight glycemic control is lifesaving. Proper counselling, proper nutrition and if regular exercise is done it can result is good glycemic control. Methods: In the present study a total of 350 diabetic patients were selected out of which only 208 participants were eligible for study. Inclusion criteria in the study were 1) Age: men and women between age group 30 years to 70 years and 2) Type 2 Diabetes mellitus with HbA1c between 8 to 10%. Exclusion criteria in the study were 1) Type 1diabetes mellitus, Pre-existing renal, hepatic or cardiac disease, Hba1c >10%. A quadriad was established between patients, personal health worker, dietician and doctor. Results: Participants had regularly followed up and were divided randomly into cases (n = 112) and controls (n = 96). Patient were followed up as per study design it was observed that at the end of 3 months period mean FBS (case group 168.2±26.4 control group 200.8±38.3 p value <0.001) , Mean PPBS (case group 204.8±53.0 control group 271.0±45.5 p value <0.001) and Mean Hba1c (case group 8.7±0.5 control group 8.9±0.6 p value .003) in cases was significantly lower than control group.at the end 6 months it was observed that the mean cholesterol, mean triglyceride, mean LDL and mean VLDL was significantly lower in the cases compared to controls. Conclusions: A systematic approach and close monitoring that increased the adherence to medication, diet, and counselling would help in better glycemic control and prevent long term complication.